Edukasi Personal Hygiene pada Remaja di Kelurahan Ampang - Mulyanti Roberto Muliantino; Rika Sarfika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Personal hygiene becomes a quite crucial problem in adolescence and is related to the physical and hormonal changes during the transition period. Adolescents still need to gain adequate knowledge regarding the changes that occur and essential personal hygiene actions. As well as education is a necessary effort to increase adolescents' knowledge. These activities aimed to improve the adolescent's knowledge of personal hygiene to increase their health and hygiene. The method used structured group education among 31 adolescents in the Ampang district of Padang City. We used the knowledge of personal hygiene questionnaire in measuring knowledge through a pre and post-test. Data analysis was presented in descriptive statistics. The result showed an increased knowledge of personal hygiene; the total knowledge of personal hygiene before education was 14.45, and after education were 18.77. Education was effective in increasing adolescents' knowledge and understanding regarding personal hygiene. In addition, they can apply their hygiene in daily life. Continuing education can be carried out in groups and individually to improve the health and hygiene of adolescents to prevent various infections.